2017
DOI: 10.1002/chem.201604655
|View full text |Cite
|
Sign up to set email alerts
|

Furan‐ and Thiophene‐Based Auxochromes Red‐shift Chlorin Absorptions and Enable Oxidative Chlorin Polymerizations

Abstract: The de novo syntheses of chemically stable chlorins with five‐membered heterocyclic (furane, thiophene, formylfurane and formylthiophene) substituents in selected meso‐ and β‐positions are reported. Heterocycle incorporation in the 3‐ and 13‐positions shifted the chlorin absorption and emission to the red (up to λ em=680 nm), thus these readily incorporated substituents function analogously to auxochromes present in chlorophylls, for example, formyl and vinyl groups. Photophysical, theoretical and X‐ray crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Thirdly, the introduction of heterocycles (such as thiophene and pyridine) in the tetracene framework can also increase its stability. 218,222 The stability of the oligomers prepared with the modied tetracene will be enhanced signicantly. Additionally, to maximize the efficiency of solar cells, it is necessary to broaden the absorption of tetracene in the red or NIR region.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the introduction of heterocycles (such as thiophene and pyridine) in the tetracene framework can also increase its stability. 218,222 The stability of the oligomers prepared with the modied tetracene will be enhanced signicantly. Additionally, to maximize the efficiency of solar cells, it is necessary to broaden the absorption of tetracene in the red or NIR region.…”
Section: Discussionmentioning
confidence: 99%
“…Connier et al reported electrogeneration and characterization of a poly(pyrrole-nickel(II) chlorin) by connecting two pyrrole units to a synthetic Ni chlorin via ester linkage, 26 while Xiong et al demonstrated electropolymerization of synthetic chlorins bearing thiophene units as reactive sites. 27 Because natural Chl-a has a vinyl group on its chlorin macrocycle, we tried to electrochemically polymerize the stable Chl-a derivatives in the initial stage of this study. A free-base chlorin, methyl pyropheophorbide-a (H 2 Chl, M = H 2 of MChl in Figure 1), 28 was attempted for electropolymerization under various conditions but no formation of polymeric films was observed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…reported electrogeneration and characterization of a poly­(pyrrole-nickel­(II) chlorin) by connecting two pyrrole units to a synthetic Ni chlorin via ester linkage, while Xiong et al . demonstrated electropolymerization of synthetic chlorins bearing thiophene units as reactive sites . Because natural Chl- a has a vinyl group on its chlorin macrocycle, we tried to electrochemically polymerize the stable Chl- a derivatives in the initial stage of this study.…”
Section: Introductionmentioning
confidence: 99%